EDUKASI ENAM LANGKAH CUCI TANGAN PAKAI SABUN “TEPUNGSELACIPUPUT” PADA ANAK USIA SEKOLAH - Siregar, Nabilah; Lismawati; Julianto; Pasaribu, Yohanna Adelina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Improper hand washing practices caused more than half of child deaths per year due to infectious diseases. This community service activity took the form of education used lecture and demonstration with musical accompaniment about six-steps hand washing exercises, and was carried out on May 18 2024 with 50 elementary school students. The results of the activity analysis showed that there was an increase in the percentage of students' ability to wash their hands in six steps with soap from 0% to 78%. Education on hand washing with demonstrations accompanied by music for children helps improve the ability of school-aged children to wash their hands so as to maintain hand hygiene and is useful in preventing disease transmission. Health workers and teachers have an important role in teaching clean and healthy living habits to improve children's health status.